COMMUNITY-BASED GASTRODIPLOMACY AND COFFEE AGROTOURISM: A CASE STUDY OF KALIANGKRIK, MAGELANG - Shabrina, Aghna Nur; Eristya, Nency Esha (BHUVANA: Journal of Global Studies, 2025)
This article explores gastrodiplomacy as a strategic approach in developing coffee-based agrotourism in Kaliangkrik, Magelang Regency, by highlighting the role of local communities in building cultural narratives through coffee. This research aims to understand how local coffee can be an instrument of public diplomacy and regional identity building. Using a qualitative interpretive method, this research is based on in-depth interviews, field observations, and literature review. The theoretical framework refers to Rockower’s concept of gastrodiplomacy and Nye’s theory of soft power. The findings show that although the practice of gastrodiplomacy has emerged organically through community-driven tourism experiences, neither the local government nor businesses have developed a systematic and sustainable strategy to promote local coffee internationally. While there have been efforts, such as geographical indication certification and promotional events, these initiatives are still fragmented and not integrated into long-term policies. This study emphasizes the need for a structured and collaborative gastrodiplomacy strategy so that local coffee can not only grow economically but also contribute to shaping the region’s cultural image at the global level.